A retrospective analysis of obstetric patient's outcome in intensive care unit of a tertiary care center - Gombar, Satinder (J Anaesthesiol Clin Pharmacol, 2014)
BACKGROUND AND AIMS: Admission to an intensive care unit (ICU) is considered as an objective marker of severe maternal morbidity. The aim was to assess the incidence and possible risk factors of obstetric patient admissions in the multidisciplinary ICU of a tertiary care center with emphasis on standardized mortality ratio (SMR). MATERIAL AND METHODS: A retrospective five year ICU record analysis was done for all pregnant women, who were admitted to multidisciplinary ICU of a tertiary care hospital during June 2007-12. RESULTS: During this 5-year period, 21,943 deliveries took place and 164 women required ICU admission. Out of these, the data of 151 patients were analyzed. Maternal mortality rate was 31.1% (47 deaths) for patients admitted to ICU. The simplified acute physiologic score (SAPS) II was 62 (55-68) in nonsurvivor versus 34.00 (28-46) in survivor group (P value < 0.001). The receiver operated characteristic curve was plotted using SAPS II scores and the area under the curve was 0.93 with 95% confidence interval (0.89-0.96). The calculated SMR was 0.97. CONCLUSIONS: Women admitted to ICU with diagnosis of puerperal sepsis and intrauterine death (IUD) with coexisting sepsis had higher mortality as compared to women with hypertensive disease of pregnancy and hemorrhage. The calculated SMR was less than one which is a predictor of good ICU care.